INFLUENCE OF MOTIVATION, WORK DISCIPLINE AND LEADERSHIP AGAINST EMPLOYEE PERFORMANCE AT THE DINAS PENGENDALIAN PENDUDUK DAN KELUARGA BERENCANA KABUPATEN LABUHANBATU - Erni Manja; Fajar Pasaribu; Hasrudy Tanjung; Satria Tirtayasa (Jurnal Ekonomi, 2023)
This research was conducted using a field research method by means of a survey, namely research that took a number of samples from the population using a questionnaire as the main data collection tool. Determination of the number of samples for this research is the total number of employees who work in the Department of Population Control and Family Planning Labuhanbatu Regency, amounting to 39 people, so this research is called population research. While the approach used is a quantitative approach, namely the approach using data analysis in the form of numeric or numbers. The aim is to develop and use mathematical models, theories or hypotheses related to the phenomena investigated by the researcher. The data analysis technique starts from collecting information through a questionnaire in the form of a statement and at the final stage by drawing conclusions. The results of the study indicate that motivation partially has a significant effect on employee performance at the Labuhanbatu Population and Family Planning Department. Work discipline partially has a significant effect on employee performance at the Labuhanbatu Population and Family Planning Department. Leadership partially has a significant effect on employee performance at the Labuhanbatu Population Control and Family Planning Service. Motivation, Work Discipline and Leadership simultaneously have a significant effect on employee performance at the Labuhanbatu Population and Family Planning Department.